1996
DOI: 10.1177/082957359601200106
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Practitioners' Errors on WIS C-R and WIS C-III

Abstract: An investigation of the difference in school psychologists' clerial error rates between WISC-R and WISC-III showed that WISC-III appears no less prone to examiner errors than WISC-R. Errors were found on 38% of WISC-R protocols and 42% of WISC-III protocols. On WISC-III, the decline in Full Scale IQ-changing errors over a period of 18 months was statistically reliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Previous studies have reported that corrected WAIS-R protocols of new examiners have not shown improvement during the first five protocols, except for errors in recording (Slate et al, 1991). Slate and Jones (1990) also found that graduate students did not show a significant error decline over five to ten practice administrations of the WISC-R. Klassen and Kishor (1996) found that the examiner errors did not decline significantly after 18 months of administering the WISC-III. In a study comparing scoring reliability of 19 psychologists and 19 graduate students on two WAIS protocols (Ryan & Schnakenberg-Ott, 2003), the percentages of protocols that fell within 1 SEM of the actual IQs were 89.5% for the psychologists and 76.3% for the students.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported that corrected WAIS-R protocols of new examiners have not shown improvement during the first five protocols, except for errors in recording (Slate et al, 1991). Slate and Jones (1990) also found that graduate students did not show a significant error decline over five to ten practice administrations of the WISC-R. Klassen and Kishor (1996) found that the examiner errors did not decline significantly after 18 months of administering the WISC-III. In a study comparing scoring reliability of 19 psychologists and 19 graduate students on two WAIS protocols (Ryan & Schnakenberg-Ott, 2003), the percentages of protocols that fell within 1 SEM of the actual IQs were 89.5% for the psychologists and 76.3% for the students.…”
Section: Discussionmentioning
confidence: 87%
“…We believe that test developers and publishers must address this issue in greater detail. Furthermore, we also concur with Klassen and Kishor (1994) that test manuals should report the scorer reliability of tests that are prone to examiner errors.…”
Section: Test Developers and Publishersmentioning
confidence: 78%
“…These types of errors decrease the reliability and validity of the obtained scores and could result in incorrect eligibility, classification, and placement decisions, which could lead to detrimental outcomes for examinees (Hall & Slate, 1992). Unfortunately, few test developers report a measure of examiner error in the form of scorer reliability (Klassen & Kishor, 1994;Ryan, Prifitera, & Powers, 1983;Slate & Jones, 1988).…”
Section: Scoring Errorsmentioning
confidence: 99%
“…(Klassen & Kishor, 1996). The requirements for the first type of scoring vary by subtest and are covered elsewhere in this chapter; for that reason, they are not described in detail here.…”
Section: Wisc-v Scoringmentioning
confidence: 97%